Ten years in the making: application of CrossMab technology for the development of therapeutic bispecific antibodies and antibody fusion proteins - Marlena Surowka; Wolfgang Schaefer; Christian Klein (Taylor & Francis Group, 2021)
Bispecific antibodies have recently attracted intense interest. CrossMab technology was described in 2011 as novel approach enabling correct antibody light-chain association with their respective heavy chain in bispecific antibodies, together with methods enabling correct heavy-chain association using existing pairs of antibodies. Since the original description, CrossMab technology has evolved in the past decade into one of the most mature, versatile, and broadly applied technologies in the field, and nearly 20 bispecific antibodies based on CrossMab technology developed by Roche and others have entered clinical trials. The most advanced of these are the Ang-2/VEGF bispecific antibody faricimab, currently undergoing regulatory review, and the CD20/CD3 T cell bispecific antibody glofitamab, currently in pivotal Phase 3 trials. In this review, we introduce the principles of CrossMab technology, including its application for the generation of bi-/multispecific antibodies with different geometries and mechanisms of action, and provide an overview of CrossMab-based therapeutics in clinical trials.